Corporate Social Responsibility - Orlando, Beatrice (IntechOpen, 2022)
This Edited Volume Corporate Social Responsibility is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in corporate behavior. The book comprises single chapters authored by various researchers and edited by an expert in the field. All chapters are complete in themselves but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors and opening new possible research paths for further novel developments.